Factors Influencing Outcome Post–Radium-223 Dichloride in Castrate Resistant Prostate Cancer: A Review of Some Real-World Challenges - Bhoil, Amit; Chuah, Phei Shan; Seshadri, Nagabhushan; Vinjamuri, Sobhan (World Journal of Nuclear Medicine, 2022)
Aim Radium-223 has been the first-approved targeted Alpha therapy agent. We retrospectively assessed different factors influencing the overall survival (OS) and patient management.Setting and Design Thirty-two metastatic castration-resistant prostate cancer (mCRPC) patients' hematological parameters, number of cycles, performance status, and toxicities were evaluated for OS. Radium 223 dichloride (Radium-223) was administered every 4 weeks for a maximum of six cycles. Primary and secondary end points were OS, progression free survival (PFS), therapy toxicities, change in performance status, biochemical response, and skeletal-related events (SREs).Materials and Methods Patients' median age was 77 years (range: 57–90 years) and median follow-up was 399 days (range: 5–1,761 days). A total of 163 cycles were administered in 32 patients, with 4 or less cycles in 8 patients (25%) and 5 or more cycles in 24 patients (75%). Among eight patients with 4 or less cycles, three patients died, of which two patients died due to neutropenic sepsis.Statistical Analysis Mann–Whitney test was used to compare the cycle groups; Spearman's correlation coefficient was used to see the relation of different variables with OS. Log rank test was used for group comparison while Kaplan–Meier survivorship was used for OS.Results Statistical correlation was seen between the number of cycles (p=0.037) and hemoglobin (p=0.028). Kaplan–Meier OS (p=0.038) was correlated with the number of cycles (≤ 4 cycles and ≥ 5 cycles). OS was 173 days in patients with one to four cycles, 226 days in five cycles, and 493 days in six cycles. Myelosuppression leading to stopping of full six cycles was seen in 7 of 32 patients (22%) and significantly correlated to inferior OS (p=0.048).Conclusion Higher number of Radium-223 cycles was seen to be associated with better OS. Prior myelosuppression was associated with poor OS. Patients with better hematological profile were more likely to complete the maximum number of the cycles with a better OS.
Keywords: Radium-223; overall survival; myelosuppression; toxicity; health economics